Chemical characterization of submicron aerosol in summertime Beijing: A case study in southern suburbs in 2018. (May 2020) - Chen, Tianzeng; Liu, Jun; Liu, Yongchun; Ma, Qingxin; Ge, Yanli; Zhong, Cheng; Jiang, Haotian; Chu, Biwu; Zhang, Peng; Ma, Jinzhu; Liu, Pengfei; Wang, Yafei; et al.
Abstract: Atmospheric particulate matters have a crucial impact on climate change, visibility and human health. In this study, a detailed characteristic of summertime PM1 was real-time measured in south suburb of Beijing from 16 th August to 16 th September 2018. Averaged PM1 concentration of 24.1 ± 18.0 μg m −3 was observed, consisting of OM (50.8%), SO4 2− (16.0%), BC (13.2%), NO3 − (10.2%), NH4 + (9.2%), and Cl − (0.6%). There was an accumulation mode with a peak diameter of ∼500 nm for all the species (except BC), and OM was additionally characterized by a smaller mode of <100 nm. Elemental analysis of OM showed that the diurnal variations of H/C, O/C, N/C, and S/C were correlated to the photochemical and aqueous-phase process. Four organic factors including one hydrocarbon-like (HOA) and three oxygenated (LO-OOA, SV-OOA and MO-OOA) organic aerosol factors were identified by positive matrix factorization (PMF) analysis. The contributions of these factors varied with PM1 concentration and their average values were 31%, 30%, 14%, and 25%, respectively. Contribution of HOA was RH-independent but decreased with the increasing PM1 concentration, while OOA factors were a combined result of RH and Ox (=O3 +NO2 ), revealing the important role of photochemical and aqueous-phase process in OA evolution. The contribution of SV-OOA with the highest S/C increased significantly with RH, indicating a certain number of S-containing organics. Our results also showed that secondary OA was the dominant species, as well as increased with the pollution level, implicating VOCs and NOx should be controlled to relieve the secondary OA pollution. Highlights: Characteristic of summertime PM1 was real-time measured in suburb of Beijing, 2018. Elemental analysis and PMF analysis of OA were resolved to expound its evolution. Role of RH and photochemical process in the evolution of PM1 species was revealed. Contribution of secondary OA increased as the pollution level during summertime.